La pêche wolastoqey à l’oursin vert : Agencement socioécologique dans l’estuaire du Saint-Laurent - Gagnon-Lewis, Charlotte; Mirza, Vincent (Anthropologica, 2024)
This research explores the rationale behind the commercial fishing of green sea urchins by the Wolastoqiyik Wahsipekuk First Nation. This fishing practice balances a number of rationales: local and global, territorial claims and foreign markets, industrial approaches and environmental concerns. The article proposes that contemporary anthropology, through the concept of assemblage, allows for a fuller understanding of the complex realities of this practice. Based on ethnographic data collected in the Bas-Saint-Laurent sea urchin industry, the article maintains that this harvest allows fishers to preserve their tenure over ancestral territory despite contemporary environmental, economic and political pressure. The article also suggests that considering this negotiation creates opportunities to rethink our food procurement methods which are ill-suited to the fluctuating realities of the contemporary world.